Prevalence of Myocardial Bridging in Angiography Study - Shakya, Smriti; Gajurel, Ratna Mani; Poudel, Chandra Mani; Shrestha, Hemant; Devkota, Surya; Thapa, Sanjeev; Manandhar, Bhawani; Khanal, Rajaram (Journal of Nepal Health Research Council, 2023)
Background: Myocardial bridging is a congenital anomaly in which a segment of epicardial coronary artery takes an intramyocardial course, the systolic compression of which could be asymptomatic or may lead to major hemodynamic changes such as myocardial ischemia, arrhythmias or sudden cardiac death. The prevalence is highly variable depending upon different investigational modalities to diagnose it. Here we have aimed to study the prevalence through invasive coronary angiography. Methods: This retrospective study was carried out at Manmohan Cardiothoracic Vascular and Transplant center, Kathmandu, Nepal. The invasive coronary angiography of 5096 patients were studied from March 2018 to April 2021 done for various indications. Results: Among all the patients, the myocardial bridging was identified in 257 (5.04%) patients. About 177 (68.9%) were males and 80 (31.1%) were females. The mean age of the patients having myocardial bridging was 54.52 ± 10.31years. Diabetes mellitus was found in 33(12.8%) and hypertension was found in 77(29.9%) patients with myocardial bridging. Stable angina (29.2%) was the most common clinical presentation. Treadmill test was positive in about 70 (27.2%) patients. Majority of patients had myocardial bridge in left anterior descending artery alone (89.9%) and located mostly in mid-part (74.9%). Conclusions: The myocardial bridging is not an uncommon finding on invasive coronary angiography in middle aged people who present with typical angina. Keywords: Coronary angiography; myocardial bridging; prevalence.